Model Analysis of Intention to Using Tije Mobile Applications For Transjakarta Users - Barimbing, Vanesha Emanuela; Astini, Rina (ADPEBI Publisher, 2023)
Purpose – This This study aims to determine and analyze the intention model using the Tije mobile application for Transjakarta users. In several previous studies, it was found that attitude mediates perceptions of convenience, perceived usefulness, and social influence on intention to use.Methodology/approaches –The method used in this study is quantitative and descriptive causal research methods. The research hypothesis testing was carried out using the Partial Least Square (PLS) based Structural Equation Model (SEM) approach.Findings – It The results showed that independently, the variables perceived convenience, perceived usefulness and social influence had a positive influence on the intention to use the Tije mobile application. The attitude variable also has a positive and significant influence on the intention to use. The three independent variables are mediated by attitudes which have a positive and significant influence on the intention to use.